An Algorithm for Coalition Formation of Swarm Aerial Vehicles Considering Communication Constraints. (December 2020) - Zhu, Mengyuan; Lv, Na; Chen, Kefan; Xue, Bin; Pan, Ying
Abstract: To realize efficient coalition formation of swarm aerial vehicles to attack static and dynamic targets on future battlefields, this study proposes a real-time dynamic network model that takes into consideration constraints in communication range and communication delay. Moreover, by using the improved particle swarm optimization algorithm for decision-making of coalition formation, the SAV resources are made best use of and the size of the coalition is minimized. The simulation result shows that in a dynamic network on the battlefield, the proposed model can realize communication and form coalitions, and the optimized algorithm shows higher efficiency than other algorithms in finding solutions. Monte-Carlo simulation result shows that when the communication delay is small, expanding the communication network to find potential coalition members can effectively reduce the time for task completion and improve the system's overall performance, but when the communication delay is large, it is better to select coalition members from neighboring SAVs.